AGENESIA OF TRACHEA - Yu.L. Soldatskiy; V.V. Volod’kina; S.A. Klochkov; I.A. Stroganov; E.K. Onufrieva (Вопросы современной педиатрии, 2010)
The article presents basic literature data on rare, potentially incompatible to life malformation of airways — agenesia or trachea. Two clinical descriptions of newborns with this pathology are presented. Key words: agenesia of trachea, tracheoesophageal fistula. (Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(3):151-153)